Recent Advances in QEPAS and QEPTS Based Trace Gas Sensing: A Review - Ma, Yufei (Frontiers in Physics, 2020)
Due to the merits of high quality factor, narrow resonance frequency band, low cost, tiny volume and immune to laser wavelength, QTF is widely used as a sensitive detector in photoacoustic spectroscopy and photothermal spectroscopy based gas sensing. In this invited review paper, the recent progress of QTF based state-of-the-art quartz-enhanced photoacoustic spectroscopy (QEPAS) and quartz-enhanced photothermal spectroscopy (QEPTS) gas sensing techniques in the past 3 years is summarized and discussed. The future development prospect of QEPAS and QEPTS based gas sensing techniques is also presented.